The True Cost-to-Serve in Nursing Homes: A Methodological Issue in Applying Activity-Based Costing - Cugini, Antonella; Caprioglio, Vanessa (Journal of Accounting and Finance, 2024)
The healthcare sector is marked by intense competition, escalating costs, service personalization, quality standards, financial constraints, and increased demand. Healthcare organizations must implement efficient cost management systems to navigate this intricate environment. The debate persists in the literature regarding the optimal cost accounting system for healthcare: traditional cost-center-based or activity-based costing (ABC). This article delves into the factors influencing the selection of a suitable cost accounting system, examining the implementation of ABC in an Italian nursing home. A methodological challenge emerged during the ABC implementation, relevant to all healthcare facilities serving diverse elderly populations. The article explores this issue, evaluates potential solutions and their impacts, and determines the approach enabling managers to accurately assess service costs and uphold service quality.